The impact of sugarcane bagasse on the biological degradation of hemp concrete - Zúniga, Arlen; Eires, Rute; Malheiro, Raphaele; Felgueiras, Helena P. (Industrial crops and products, 2024)
This study evaluates the biological resistance of hemp concrete (HC) combined with sugarcane bagasse (SCB), a residue widely available in sugar-producing countries and relevant for the development of eco-friendly materials that promote the circular economy. Observational tests were carried out to promote the growth of microorganisms and assess resistance to specific bacteria such as Bacillus subtilis and Micrococcus luteus, and fungi such as Cladosporium herbarium, Penicillium chrysogenum, and Candida tropicalis. HC, due to the alkalinity of lime, exhibits natural resistance to microorganisms; however, the addition of SCB can alter this property. It was found that high percentages of lignin in hemp increase its biological resistance, while SCB, with a higher proportion of cellulose and hemicellulose and lower lignin content, is more susceptible to microbial attack. A correlation was also established between the capillarity coefficient and susceptibility to degradation, essential for designing balanced materials. It was observed that including up to 50 % SCB in the HC mix provides mechanical benefits without significantly affecting biological resistance, demonstrating effective inhibition against airborne fungi. Nevertheless, increasing SCB above 25 %, depending on the lime ratio, reduces resistance to degradation by the specific microorganisms evaluated. This study focuses on a little-studied subject, the evaluation of the biological degradation of natural-based building materials, and the main innovation is the evaluation of the combination of HC with SC. These results could offer new guidelines for the formulation of mixtures using natural fibers and agricultural waste, which are crucial for the development of bio-based building materials. •Hemp's physicochemical properties resist degradation more than sugarcane bagasse.•Sugarcane ashes require treatment due to potential organic material contamination.•Higher sugarcane bagasse proportion leads to lower biological degradation resistance.